The emergence of novel SARS-CoV-2 variant P.1 in Amazonas (Brazil) was temporally associated with a change in the age and gender profile of COVID-19 mortality - Freitas, Andre Ricardo Ribas (2021)
Background Since the end of 2020, there has been a great deal of international concern about the variants of SARS-COV-2 B.1.1.7, identified in the United Kingdom; B.1.351 discovered in South Africa and P.1, originating from the Brazilian state of Amazonas. The three variants were associated with an increase in transmissibility and worsening of the epidemiological situation in the places where they expanded. The lineage B.1.1.7 was associated with the increase in case fatality rate in the United Kingdom. There are still no studies on the case fatality rate of the other two variants. The aim of this study was to analyze the mortality profile before and after the emergence of the P.1 strain in the Amazonas state. Methods We analyzed data from the Influenza Epidemiological Surveillance Information System, SIVEP-Gripe (Sistema de Informação de Vigilância Epidemiológica da Gripe), comparing two distinct epidemiological periods: during the peak of the first wave, between April and May 2020, and in January 2021 (the second wave), the month in which the new variant came to predominate. We calculated mortality rates, overall case fatality rate and case fatality rate among hospitalized patients; all rates were calculated by age and gender and 95% confidence intervals (95% CI) were determined. Findings We observed that in the second wave there were a higher incidence and an increase in the proportion of cases of COVID-19 in the younger age groups. There was also an increase in the proportion of women among Severe Acute Respiratory Infection (SARI) cases from 40% (2,709) in the first wave to 47% (2,898) in the second wave and in the proportion of deaths due to COVID-19 between the two periods varying from 34% (1,051) to 47% (1,724), respectively. In addition, the proportion of deaths among people between 20 and 59 years old has increased in both sexes. The case fatality rate among those hospitalized in the population between 20 and 39 years old during the second wave was 2.7 times the rate observed in the first wave (female rate ratio = 2.71; 95% CI: 1.9-3.9], p <0.0001; male rate ratio = 2.70, 95%CI:2.0-3.7), and in the general population the rate ratios were 1.15 (95% CI: 1.1-1.2) in females and 0.78 (95% CI: 0.7-0.8) in males]. Interpretation Based on this prompt analysis of the epidemiological scenario in the Amazonas state, the observed changes in the pattern of mortality due to COVID-19 between age groups and gender simultaneously with the emergence of the P.1 strain suggest changes in the pathogenicity and virulence profile of this new variant. Further studies are needed to better understanding of SARS-CoV-2 variants profile and their impact for the health population.